Membangun Pembelajaran Interakti Pengembangan dan Penerapan Video 3D Animation Berbasis AI dengan Teka-Teki Silang Wordwall untuk: Evaluasi Materi Akidah Akhlak Kelas X MAN 2 Jombang - Firdaus, Rubayyi Rubayyi (Maliki Interdisciplinary Journal, 2024)
Interactive learning has become a major focus in the development of modern education, especially in combining advanced technologies such as artificial intelligence (AI). Technological developments have shifted the learning paradigm, thereby encouraging research into methods that are more interactive and interesting for students. This research method uses a qualitative method where reading, research, observation and direct action are carried out in the classroom which can be described. This article discusses the development and application of AI-based 3D animated videos accompanied by Wordwall crossword puzzles as an evaluation tool in learning moral belief material for class X at MAN 2 Jombang. This research aims to determine the effectiveness of combining advanced technology in increasing students’ understanding of the material as well as their enthusiasm and motivation for learning. The development method used involves integrating AI into 3D animation to create an immersive and interactive learning experience. The implementation results show that the combination of 3D animated videos and Wordwall crossword puzzles succeeded in increasing students’ enthusiasm and enthusiasm for learning, providing a fun and interactive learning experience. The implication of this research is that the application of technology in learning can be an effective means of advancing the quality of education in this digital era.